First record of the presence of antibodies against Leptospira in Lagostomus maximus, and Leptospira weillii serogroup Celledoni in Chaetophractus villosus, Argentina - Kin, Marta Susana; Sanchez, Maria Cristina; Esteban, Micaela; Martinez, Mara Leila; Brihuega, Bibiana Felicitas; Hamer, Micaela; Saraullo, Vanina Rosa; Cayron, Eduardo D.; Cayron, Gabriel P.; Gimenez, Hugo Daniel; Cayron, Carlos R.; Fort, Marcelo Cristian (Elsevier, 2025)
Leptospirosis is a zoonosis with a worldwide distribution, which is transmitted through direct contact with infected animals or by contact with contaminated water or soil. Objectives was to examine the presence of antibodies against 23 serogroups of Leptospira in Lagostomus maximus and Chaetopractus villosus in La Pampa province, Argentina. Ninety-four serum samples from L. maximus (80) and C. villosus (14) were taken. The samples were analysed by microscopic agglutination test (MAT). Only 5/94 (5.3 %) serum samples presented antibodies against Leptospira sp. Three (21.4 %) serum samples from C. villosus, were reactive to the serogroups, Ballum, Grippotyphosa, Canicola and Celledoni, and two samples (2.5 %) of L. maximus to Pomona, Canicola and Ballum. This constitutes the first record of the presence of antibodies serogroup Celledoni in C. villosus and serogroups Pomona, Canicola and Ballum in L. maximus in Argentina.